Effect of a probiotic mix supplementation on the productive performance of growing and finishing guinea pigs (Cavia porcellus) - Cano W., Javier (2016)
The study evaluated the effect of addition of a probiotic mix in the diet on body weight gain, feed intake and feed conversion of growing and finishing guinea pigs. A total of 64 male guinea pigs, 1 day-old from an experimental farm in Huncayo, Peru were selected. The animals were randomly allocated to four feed treatments consisting of a rye grass-clover forage basal diet supplemented with wheat bran plus 0, 100, 150 or 200 ml of a Lactobacillus-Bifidobacterium-Saccharomyces probiotic mix suspension. The probiotic was mixed with 1 kg of the supplement and supplied during 10 weeks. Significant linear response patterns to the probiotic levels were observed for body weight gain (y = 631.04571 + 0.60537x; r2=0.2971, p=0.029) and feed conversion (y = 6.21121 - 0.0339x; r2=0.625, p=0.0003). There was no significant effect on feed intake. It is concluded that the probiotic mix has the potential for improving the productivity and feed efficiency of guinea pigs, but higher levels should be explored in order to obtain biological and practical optimal results.